2006
DOI: 10.1007/s11240-006-9109-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of Light and Medium Composition on Growth and Valepotriate Contents in Valeriana glechomifolia Whole Plant Liquid Cultures

Abstract: A system for growing in liquid medium whole plants of Valeriana glechomifolia, endemic to southern Brazil and capable of accumulating bioactive valepotriates, is described. Murashige and Skoog (MS) and Gamborg B5 (B5) media (1.0·, 0.3· and 0.1· strength) without phytohormones were evaluated after four weeks of culture in relation to growth and valepotriate yield. Plants grown in 1.0· MS displayed greatest growth and valepotriate yields and the study of the light condition showed that plants grown under light a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
5
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
6
5
1
Order By: Relevance
“…In both media higher dry weight values were obtained by roots grown in half strength MS and MSV media, 2.22 to 1.62 g l -1 and 2.658 to 2.01 g l -1 , respectively. These results are in contrast with the results of Russowski et al (2006) that studied the growth of whole plant in liquid culture and Chen et al (2003) for taxol production in cell cultures of Taxus yunnanensis. High concentrations of inorganic nutrients in the full strength MS and MSV media may be the cause of these results.…”
Section: Effect Of Basal Medium On Hairy Root Growthcontrasting
confidence: 99%
“…In both media higher dry weight values were obtained by roots grown in half strength MS and MSV media, 2.22 to 1.62 g l -1 and 2.658 to 2.01 g l -1 , respectively. These results are in contrast with the results of Russowski et al (2006) that studied the growth of whole plant in liquid culture and Chen et al (2003) for taxol production in cell cultures of Taxus yunnanensis. High concentrations of inorganic nutrients in the full strength MS and MSV media may be the cause of these results.…”
Section: Effect Of Basal Medium On Hairy Root Growthcontrasting
confidence: 99%
“…The overall results confirm, for long-term cultures in solid media, the direct relationship between growth and valepotriate production previously established for shorter term whole-plant, cell and root cultures of V. glechomifolia grown in liquid media Russowski et al 2006). Moreover, the media modifications in M Δ were able to significantly enhance growth and production of valepotriates, maintaining physiological viability and providing an adequate formulation for long-term stock cultures.…”
Section: Resultssupporting
confidence: 85%
“…Further studies analyzed the growth kinetics and the influence of the auxins indole-3-acetic acid, indole-3-butyric acid, and α-naphthaleneacetic acid in micropropagated V. glechomifolia and survival under ex vitro conditions after plant acclimatization (De Carvalho et al 2004). Production of valepotriates has also been studied in V. glechomifolia tissue cultures, such as callus, cell suspension, and root cultures ; the roles of light and medium composition on growth and valepotriate contents in whole plants cultured in liquid medium were also investigated (Russowski et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported the value of liquid media for shoot multiplication (Russowski et al 2006;Pati et al 2011;Cavallaro et al 2014). However, S. alpina shoot tip explants placed in liquid culture, either agitated or stationary, did not derive shoots, and tissue necrosis was observed, probably caused by the continuous contact between the plant tissue and the liquid medium.…”
Section: Shoot Multiplicationmentioning
confidence: 99%